Study of Application of Robotics in Spinal Surgery - Ong, Zhi Inn (Transactions on Computer Science and Intelligent Systems Research, 2024)
Pedicle fixation during spinal surgery done with robot assistance has sparked a wave of contemporary discourse within the surgical field. This contrasts with conventional methods such as freehand with fluoroscopy assistance. The comparison between the novel and conventional techniques, the gradual application of robotics into spine surgical field, prospects, and limitations of applying robotics in spinal surgery will be discussed in this review. Spine surgery with robot assistance was shown to have lowered the risk of surgical spine in multiple aspects including radiation exposure, neurologic/vascular damage due to its high precision. The first established of robotics into the system which had pioneered the field and which subsequently led to more innovative technologies that target the conveniency, accuracy and duration for incorporating robots into spinal surgery procedure. With the acceleration of inventions and reduced intervals between their emergences, had drawn some attention to the learning curves associated with the application of robotics in spinal surgery. Albeit the many flaws being refined with robot assistance during spinal surgery, however, the effect as compared to other techniques is still not as prominent and impactful thus, leading to the slow progressing of incorporation into the spinal surgical field.